Long-term evaluation of otosclerosis on temporal bone CT - Döring, Katja; Satyavolu, Syam; Durisin, Martin; Götz, Friedrich; Lanfermann, Heinrich; Warnecke, Athanasia; Giesemann, Anja (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
To assess the long-term progression of otosclerosis lesions on temporal bone CT, particularly with regard to lesion expansion, distribution, and changes in density.This retrospective study analyzed all patients who underwent HRCT or CBCT for the diagnosis of otosclerosis between 2012 and 2022. The study population was screened for the presence of follow-up imaging. Patients with available imaging over a period of five years were included in the study. Demographic data, clinical symptoms, and imaging findings were analyzed using descriptive statistics. The imaging findings were grouped according to otosclerosis subtype (fenestral, retrofenestral, or internal auditory canal (IAC)) and the long-term course of otosclerosis was assessed in terms of density and size.35 patients were included in a follow-up study with an average duration of 100 months (range: 62–168 months, 5 to 14 years ) for otosclerosis. A total of 65 ears were affected. The patients were on average 48 ± 12.1 (range: 11–74) years old. Women (n= 24, 69%) were more than twice as likely to be affected as men (n= 11, 31%). Retrofenestral otosclerosis was the most common form (54%), followed by fenestral otosclerosis (40%). Otosclerosis around the IAC was significantly less common, accounting for just 6% of cases. In both fenestral and retrofenestral otosclerosis, an increase in otosclerotic volume between the initial and last follow-up imaging scans was observed in fewer than a third of cases (16% vs. 20.6%; Table 2). The density increased in some cases over time, affecting 24% of fenestral and 38.2% of retrofenestral cases. If the IAC was affected, imaging showed no changes in extent or density over time.Over the long term (five to 14 years), slight changes in density (increasing sclerosis) and size expansion can only be observed in approximately one third of patients. A progression from fenetral to retrofenestral otosclerosis was not documented in any of the cases.
Keywords: otosclerosis; long-term follow-up; SNHL; CBCT; HRCT